Leadership Of Madrasah Heads In Improving The Quality Of Educational Institutions In East Java, Indonesia - Wahib, Abd. (CV. Inara, 2024)
To determine the leadership of madrasah heads in improving the quality of educational institutions at MAN 1 Bojonegoro, East Java, Indonesia. This research uses a qualitative approach with field research and uses a case study design. The research location is MAN 1 Bojonegoro, East Java, Indonesia. Data was obtained from school principals, leaders of MAN 1 Bojonegoro, East Java, Indonesia, staff and teachers. The data collection methods used were participant observation, in-depth interviews and documentation. The data analysis method used is data reduction, data presentation, drawing conclusions. From this research, the research results can be seen, namely: 1) The head of the madrasah in mobilizing to improve the quality of educational institutions at MAN 1 Bojonegoro, East Java, Indonesia by means of; participate in preparing lesson plans, select teachers who are competent in guiding students in self-development, provide motivation to subordinates, form team work (cooperation), coordinate task activities for participating in training, the head of the madrasah also holds meetings with subordinates, and provide motivation to subordinates by setting a good example. 2) The leadership of the madrasa head in directing the improvement of the quality of educational institutions at MAN 1 Bojonegoro, East Java, Indonesia by means of; the head of the madrasah motivates teachers to be more creative, and coordinates the results of their work, the head of the madrasah always evaluates teacher activities, and holds official meetings with subordinates, by providing motivation to teachers during official meetings, the head of the madrasah gives a task to teachers to take part in training, the head of the madrasah gives the task of making lesson plans to teachers, the head of the madrasah also gives good role models to subordinates to be an example of hard work for subordinates, 3) Leadership of the head of the madrasah in influencing the improvement of the quality of educational institutions at MAN 1 Bojonegoro Java Eastern Indonesia by means of the head of the madrasah giving an award to teachers who excel in guiding students, the head of the madrasah provides role models and provides attention, provides welfare, provides a good example, motivates subordinates, the head of the madrasah supports and gives appreciation for achievement to his subordinates.